Potential Investment In The Food Crop Sub-Sector In Barito Kuala - Ali Wardhana; Deasy Arisanty; Asrid Juniar (JPG (Jurnal Pendidikan Geografi), 2025)
This study aims to identify investment opportunities in leading food crop sub-sectors in Barito Kuala Regency. The data used in this study are secondary data sourced from the Central Statistics Agency of South Kalimantan Province, covering time series data from 2019 to 2024. The analytical method employed is quantitative, using the Location Quotient (LQ) formula. The leading food crop commodities in Barito Kuala Regency are: first, rice, which has been a base sector from 2019 to 2024 with an average LQ value of 1.3143; second, cassava, which has also been a base sector over the same period with an average LQ value of 1.9574; and third, soybeans, which became a base sector during 2021–2022 with an average LQ of 1.3004. Both the government and private sectors can further develop rice into processed industries such as packaged rice, rice flour, and food industries. Investment opportunities for cassava include snack food industries, tapioca flour, animal feed, MSG, and synthetic sugar industries. Meanwhile, soybeans show potential for large-scale cultivation expansion.